2020
DOI: 10.3390/en13184776
|View full text |Cite
|
Sign up to set email alerts
|

Polysilane-Inserted Methylammonium Lead Iodide Perovskite Solar Cells Doped with Formamidinium and Potassium

Abstract: Polysilane-inserted CH3NH3PbI3 perovskite photovoltaic devices combined with potassium and formamidinium iodides were fabricated and characterized. Decaphenylcyclopentasilane layers were inserted at the perovskite/hole transport interface and annealed across a temperature range of 180–220 °C. These polysilane-coated cells prevented PbI2 formation, and the conversion efficiencies were improved over extended periods of time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 59 publications
0
23
0
Order By: Relevance
“…By incorporating DPPS between the perovskite and HTL, effective hole transport from the valence band of the perovskite to the Au electrode was induced. This smooth transport was also due to the molecular structure of DPPS [13,16,38].…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…By incorporating DPPS between the perovskite and HTL, effective hole transport from the valence band of the perovskite to the Au electrode was induced. This smooth transport was also due to the molecular structure of DPPS [13,16,38].…”
Section: Resultsmentioning
confidence: 90%
“…The perovskite compounds were prepared by mixing N,N-dimethylformamide (DMF; Sigma Aldrich) solutions of KI (Wako Pure Chemical Industries), HC(NH2)2I (Tokyo Chemical Industry, Tokyo, Japan), CH3NH3I (Tokyo Chemical Industry), and PbCl2 (Sigma Aldrich) at 60 °C for 1 day. The basic precursor of MAPbI3 was prepared with molar concentrations of PbCl2 and MAI of 0.8 and 2.4 M, respectively [41,43], and MA0.64FA0.31K0.05PbI3 and MA0.48FA0.47K0.05PbI3 precursors were prepared by adding FAI and KI to control the desired molar ratio [38]. As the FA composition increased, the tolerance factor (t-factor) increased toward 1 [19], which indicated the crystal distortion in the perovskite structure could be reduced by FA addition.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8] The photovoltaic performance was based on optimization with tuning of the electronic structure, band gap, and the effective mass related to the carrier mobility. For example, the incorporation of an alkali metal, [9][10][11][12] organic cation, 13,14 transition metal, [15][16][17][18][19][20][21][22][23] tin, 24,25 and halogen ion, 26,27 improved the photovoltaic performance based on the surface modification, and promotion of the crystal nucleation and growth in the perovskite layer. The perovskite solar cells had many problems to solve regarding the long-term stability of the photovoltaic performance for practical use of the photovoltaic devices.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the photovoltaic properties of perovskite solar cells depended severely on the compositions and crystal structures of the perovskite compounds. Doping with such elements as cesium [5], rubidium [6,7], potassium [8][9][10], sodium [11], formamidinium (CH(NH2)2, FA) [10,12], ethylammonium (CH3CH2NH3, EA) [13], or guanidinium (C(NH2)3, GA) [14][15][16] at the methylammonium (CH3NH3, MA) sites improved the conversion efficiencies. Studies on doping with halogen atoms, such as chlorine (Cl) [17][18][19][20][21][22][23] or bromine (Br) [6], at the iodine (I) sites of the perovskite crystals have also been reported.…”
Section: Introductionmentioning
confidence: 99%